PENGARUH PENAMBAHAN ZAT ADIKTIF PADA PREMIUM TERHADAP POLUSI UDARA KENDARAAN BERMOTOR - Setiawan, Yudi; Wijianti, Eka Sari (Mesin, 2016)
The increasing use of motor vehicles will increase fuel consumption thus impact on the increase in air pollutants, especially carbon monoxide (CO) and hydrocarbons (HC) produced from residual products of combustion vehicles. The flue gas coming from motor vehicles in excessive levels would be harmful to both human health and the environment. However, with the increasing population of the use of motor vehicles will also increase. Research on a mixture of methanol and acetone with a premium in order to determine the effect of variations in a mixture of methanol and acetone with a premium on exhaust emissions, density and flow rate of fuel to the variation of fuel mixture Acetone 4%, Acetone 8%, Methanol 4%, Methanol 8 % and the engine turns 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm. Acetone and methanol can reduce the levels of CO and HC. CO produced the lowest in 8% methanol mixture at 2000 rpm rotation that is equal to 2.6%. HC produced the lowest in 8% methanol mixture at 5000 rpm rotation that is equal to 131 ppm. Increasingly rising engine turns the CO content increases, while the HC will decrease. A mixture of acetone and methanol with a premium can reduce fuel consumption. But along with the increase in the engine rotation time fuel consumption decreased. Time highest fuel consumption resulting in pure premium round 2000 rpm is for 141.23 seconds. The lowest fuel flow rate resulting in pure premium round 2000 rpm is for 0175 kg / hour.Key Word : emision, metanol, etanol